A büntetőjog normalizálódása és az abolíció eszméjének térhódítása Magyarországon: a halálbüntetés szabályozása a ’60-as évek elejétől a ’80-as évek végéig - Tóth J., Zoltán (Debreceni Jogi Műhely, 2007)
The capital punishment was poena ordinaria throughout the history of Hungary. Nevertheless, it was applied most frequently not in the Middle Ages, but in the 20th century. There have never been so many legal executions in our country, than during the World War One and Two, however in lack of reliable statistical data the precise number of the death penalties is not known even in recent years. There were numerous death penalties imposed in the Fifties as well, mainly in the years of retaliation after the Revolution of 1956. Only in 1961 did the situation get back to normal, when implementation of martial law stopped for good and all. In this year the Parliament of the People’s Republic of Hungary passed the Act V of 1961 on the Criminal Code that permitted the infliction of the death penalty for altogether thirty-one criminal offenses (for nine crimes against the state, two crimes against peace and humanity, eight military offenses and twelve common offenses), but this sanction in no cases was qualified as compulsory, the judge had the possibility to impose an imprisonment sentence for 10-15 years in each times. The Criminal Code’s Amendment, the Law Decree No. 28 of 1971 reduced the number of the crimes punishable by death to twenty-six, although a new capital felony, seizure of aircraft, was introduced as well. In 1978 a new Criminal Code, namely the Act IV of 1978, was drafted in which death was also ordered for twenty-six offenses, of them for a new one, Act of Terrorism. Meanwhile the number of the death penalties carried out persistently decreased (in the Sixties there were 129 executions, in the Seventies there were 47 and in the Nineties there were 32). However, the process of the abolition actually started only in 1983 when a conference was organized by the Hungarian Lawyers Alliance to discuss the future of the capital punishment in the Hungarian criminal law. Nevertheless, the Hungarian abolitionist movement gained strength in deed when the League Against Capital Punishment was formed in 1989. In the subsequent year the League asked the newly established Hungarian Constitutional Court to declare the death penalty unconstitutional on the ground that it was contrary to the right to life protected by Article 54 of the Hungarian Constitution. Eventually this happened in 1990 by Constitutional Court Decision No. 23-AB of 31 October 1990. From this time the practice of capital punishment is irrevocably forbidden in Hungary.